Metode Mudarasah sebagai Upaya Peningkatan Menjaga Hafalan Al-Quran - Fikriyyah Qothrun Nadaa (Al-Liqo: Jurnal Pendidikan Islam, 2021)
Mudarasah is peer listening of Al-Quran memorization to other people in turn and at the group perverse or several verses as settled by the teacher. This method is one of the efforts to always maintain memorization for a hafiz. "Al-Quran is sacred, whoever keeps it will be sacred", that was the message of the teachers to their students. The awareness of a hafiz to always Murajaah, fix, and maintain his memorization becomes an obligation.